2020
DOI: 10.1021/acs.energyfuels.9b02275
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Surfactant–Polymer/Alkaline–Surfactant–Polymer Formulation for Enhanced Oil Recovery (EOR) Processes

Abstract: An extensive investigation into the applicability of poly­(vinyl alcohol) (PVA) and its synergy with rhamonolipid (a surfactant-active agent) and/or an alkali (NaOH) was carried out to evaluate and define the best fluid formulation for enhanced oil recovery (EOR) processes. First, the effects of molecular weight, concentration, and temperature of the PVA solution on surface tension (ST), interfacial tension (IFT), apparent viscosity, and thermodynamic stability were determined. Then, a systematic formulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Typical formulations used for enhanced oil recovery have been recently reported by Ramos et al [ 30 ]. These present concentrations of polymers and surfactants range between 0.1 and 0.3% w / w and 100 and 250 mM, respectively, and in general brine is used instead of pure water, which allows fixing the ionic strength.…”
Section: Methodsmentioning
confidence: 99%
“…Typical formulations used for enhanced oil recovery have been recently reported by Ramos et al [ 30 ]. These present concentrations of polymers and surfactants range between 0.1 and 0.3% w / w and 100 and 250 mM, respectively, and in general brine is used instead of pure water, which allows fixing the ionic strength.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the synergy between nano-sized crosslinked polymeric particles with low salinity water can lead to ultra-low interfacial tensions and huge (> 62 %) oil recovery [49]. In a study, the combination of poly(vinyl alcohol)-rhamonolipid and NaOH−rhamonolipid−PVA in saline EOR medium was found to significantly reduce the surface tension and IFT [50]. Similarly, a polyacrylates/amorphous carbon thin film composite recovered 19.2 % of residual oil saturation [51].…”
Section: Synergy With New Formulationsmentioning
confidence: 99%
“…In addition, Imaoka et al prepared the PNaAMPS/PAAm double-network (DN) gel formed by the main network (2-acrylamido-2-methylpropanesulfonic acid sodium salt) (PNaAMPS) and the secondary network polyacrylamide (PAAm), in which unique mechanical-swelling coupling will promote the application of DN materials in harsh mechanical environments. Based on polyvinyl alcohol (PVA) thermal stability, salinity resistance, and biocompatibility, , Wu et al prepared a PVA/glycerol hydrogel subjected to solvent exchange and wet annealing to reconstruct the hydrogel network structure to achieve a tough, anti-fatigue hydrogel with high chain entanglements and crystallinity; the related PVA products also have certain application prospects in oilfield chemistry. In our previous research work, a self-healing PVA composite gel was prepared, and the simulated core displacement device showed that it had better water plugging performance.…”
Section: Introductionmentioning
confidence: 99%